Graphene-Based Electronically Tuneable Microstrip Attenuator. (24th June 2014) - Pierantoni, L.; Mencarelli, D.; Bozzi, M.; Moro, R.; Bellucci, S.
This paper presents the design of a graphene-based electronically tuneable microstrip attenuator operating at a frequency of 5 GHz. The use of graphene as a variable resistor is discussed and the modelling of its electromagnetic properties at microwave frequencies is fully addressed. The design of the graphene-based attenuator is described. The structure integrates a patch of graphene, whose characteristics can range from being a fairly good conductor to a highly lossy material, depending on the applied voltage. By applying the proper voltage through two high-impedance bias lines, the surface resistivity of graphene can be modified, thereby changing the insertion loss of the microstrip attenuator.